Promoción de crecimiento de Calibrachoa mediante la aplicación de aislados de Trichoderma - Borrelli, Nicolás Pablo; Karlanian, Monica; Rubio, Esteban Julian; Leva, Paula Edit; Pitarch, Ruben Carlos; Rivera, Marta Carolina (Universidad Nacional de Hurlingham, 2025)
Poster